Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/aogs.12529
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of antepartum and intrapartum hemorrhage to the burden of maternal near miss and death in a national surveillance study

Abstract: Severe maternal outcome due to antepartum and intrapartum hemorrhage was highly prevalent among Brazilian women. Certain risk factors, maternal age and previous cesarean delivery in particular, were associated with the occurrence of bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
2
15
0
1
Order By: Relevance
“…A deficiency in prenatal care, which can lead to complications during pregnancy, is a reality in Brazil and has been reported in other studies. 10,13,14 Inthepresentstudy,568(64.5%)ofwomenwithsevere maternalmorbidityand54(88.5%)ofwomenwithnearmissordeath hadattendedfewerthansixprenatalappointments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A deficiency in prenatal care, which can lead to complications during pregnancy, is a reality in Brazil and has been reported in other studies. 10,13,14 Inthepresentstudy,568(64.5%)ofwomenwithsevere maternalmorbidityand54(88.5%)ofwomenwithnearmissordeath hadattendedfewerthansixprenatalappointments.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the two study groups demonstrate clinical severity, which makesthemsimilartoacertainextent.Third,neitherthetimetaken before thesewomen received health care nor the therapeutic route leading to their admission was evaluated; these factors are known to be related to poorer maternal and neonatal results. [12][13][14][22][23][24] Additionally, data for newborns were missing from some medical records. The study has strengths.…”
Section: Resultsmentioning
confidence: 99%
“…However, a medically inappropriate CS is associated with a higher risk of perinatal and maternal mortality than is a vaginal delivery [1]. Studies have found that most cases of obstetric hemorrhage and emergency postpartum hysterectomy were associated with previousCSdeliveries [2]. Due to the surgical nature of CS, after controlling for indication bias and confounders, the risk of postpartummaternaldeath is almost three-fold higher than that associated with vaginal delivery; these maternal deaths are mainly due to postpartum hemorrhage and complications of anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…A case of "Near miss maternal" is defi ned as the patient at risk of dying, but survives a complication that occurred during pregnancy, delivery or at the end of the puerperium or 42 days of termination of pregnancy; are those women who have survived life-threatening conditions (due to organic dysfunction). The indicators of processes are those that advise the mechanisms in the care of the health; The key to interventions related to the prevention and management of severe maternal complications will be used as a key to implement recommendations based on evidence [15,19].…”
Section: Severe Obstetric Morbidity (Near Miss) Backgroundmentioning
confidence: 99%